Nativization Process and its Effects on the Phonology of Rampuri Urdu: A Sociolinguistic Study - Malik, Nazish (Nepalese Linguistics, 2022)
Generally, a language, to enrich its grammar and vocabulary, does borrowing at the level of sound, grammar, and meaning through the process of nativization. The objective of this research paper is to observe nativization effects mainly at the level of sound and briefly at the level of grammar in the speech data of Rampuri Urdu. For instance, the Arabic word /əxbar/ ‘newspaper’ has been nativized with the transition of sound as /əkʰbar/ ‘newspaper’ in Rampuri Urdu.